Epidemiological study of Giardiasis and its impact on children blood picture - Rafid abdalwahed abdalnabi; Bakr farouk sabih (College of Pharmacy / Mustansiriyah University, 2012)
A total of 106 blood samples and 350 fecal samples were collected from children for the period from beginning of June till the end of November 2010 for this study. The higher infection of Giardia. lamblia was 49.35% in patients visit Abughraib hospital while the lowest was 26.11% patients visit central health laboratories. There is no significant difference noticed between two sexes (male, female) the infected rate in male was 31.42%, while in female 32.14% . This study showed the relation between infection rate and the age, the age of 6-10 years old showed highest infection rate were 66.66% while the lowest rate of infection 4.08 % at age of 1-3months. The study showed a clear effect of Giardiasis on rate of packed cell volume it was in infected children 39.14 % while in non infected 31.91% There is also effect of Giardiasis on rate of children hemoglobin it was in infected 11.87gm /100 microlitter while in non infected was 10.05gm/100 microlitter. This study showed effect of Giardiasis on Total white blood cells it were in infected children 700 Cells/microlitters while in non infected were 785 cells/microlitter.